2018
DOI: 10.3390/educsci8040168
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Middle School Organizational Structures in the United States and Australia

Abstract: The middle school concept, aimed at creating a more developmentally responsive learning environment for young adolescents, gained a stronghold in the later part of the 20th century. Proponents of this concept have argued continually for the holistic implementation of its six key characteristics if its benefits are to be realized. These characteristics include: (a) a challenging, integrative, and exploratory curriculum; (b) varied teaching and learning approaches; (c) assessment and evaluation that promote lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In Australia, since the beginning of the 20th century, the dominant secondary school organisational model has been that of the subject departmental structure (Brady, 2010; Ellerbrock et al, 2018; Woolner et al, 2014). These organisational departments are purposely created to deliver specialised knowledge and competencies to students but can also promote insular behaviour and maintain departmental boundaries, at the expense of school improvement agendas.…”
Section: Organisational Structure That Tends To Promote Isolation Andmentioning
confidence: 99%
“…In Australia, since the beginning of the 20th century, the dominant secondary school organisational model has been that of the subject departmental structure (Brady, 2010; Ellerbrock et al, 2018; Woolner et al, 2014). These organisational departments are purposely created to deliver specialised knowledge and competencies to students but can also promote insular behaviour and maintain departmental boundaries, at the expense of school improvement agendas.…”
Section: Organisational Structure That Tends To Promote Isolation Andmentioning
confidence: 99%
“…They mentioned two types, which are physical and social structures. Similarly, Ellerbrock et al (2018) studied three types in their paper, the people (social) structure, the place (physical) structure, and the time structure. Structure of time is a unique type, placing importance on how time is allocated for learning.…”
Section: Organizational Structure and The Schoolmentioning
confidence: 99%
“…According to a report by the American Education Research Association (2016), more investigation is needed into what school structures are effective for middle schools. Although block scheduling was well represented in the data before 2000 this topic has rarely been found in the literature since then (Ellerbrock, Main, Falbe, & Franz, 2018). There is new urgency to investigate different time structures to help students achieve the more rigorous state standards related to the Common Core Standards.…”
Section: Introductionmentioning
confidence: 99%
“…Patall et al (2010) suggested that educational researchers conduct a well-designed research that will help determine under what condition, for whom, and when more instructional time will yield the greatest student achievement. The gap in the literature suggested by Patall et al (2010) and Ellerbrock, Main, Falbe, and Franz (2018) guided this investigation to determine if more frequent instructional time in mathematics will yield greater student achievement and decrease the achievement gap in mathematics.…”
Section: Introductionmentioning
confidence: 99%